Forecasting Optimisation using Linear Programming - HUANG, DANFENG (2010)
The main aim of this project is to investigate forecasting methods using linear programming approach to optimise the forecast. And the objective function and constraints are also explored. In which, the accuracy and optimized parameter of forecasting models are recorded from different conditions experiments setup. The time series data are investigated and sorted in the similar group to compare and analyse. Two main software Excel and LINGO also will be introduced in this project, which helps to measure the accuracy.